A framework for social tipping in climate change mitigation: What we can learn about social tipping dynamics from the chlorofluorocarbons phase-out. (December 2021) - Stadelmann-Steffen, Isabelle; Eder, Christina; Harring, Niklas; Spilker, Gabriele; Katsanidou, Alexia
Abstract: In the natural sciences, the concept of "(natural) tipping points" has become a hot topic in climate change research. To better understand and evaluate the possibilities for and the barriers to the fundamental societal transformations necessary for climate change mitigation, we suggest a social tipping dynamics framework. We contrast this framework with previous accounts of stability and change and show that integrating these approaches under the umbrella of a social tipping dynamics framework provides us with a more encompassing and therefore more realistic account for theorizing and empirically analyzing the different (technological, behavioral, and political) paths and related interdependencies to fundamental societal change. Moreover, by emphasizing the agency aspect, we highlight that the type of fundamental change required in effective climate change mitigation is more strongly actor-driven than previous approaches have suggested. In a second step, we apply our framework to the phase-out of chlorofluorocarbons and thereby illustrate its merits. To conclude, we summarize the value of the concept of social tipping dynamics, including its limitations and potential for improving political analysis.